X-ray Structures of 3-Acetyloxazolidin-2-one, 3-Acetyloxazolin-2-one and Oxazolin-2(3H)-one - R. Alan Aitken; Joe S. Logan; Alexandra M. Z. Slawin (Molbank, 2022)
The X-ray structures of three simple heterocyclic compounds have been obtained for the first time. Structures of both 3-acetyloxazolidin-2-one 1 and its unsaturated analogue 3-acetyloxazolin-2-one 3 show a planar imide nitrogen with the exocyclic C=O oriented anti to the ring N–C(=O) bond and negligible intermolecular interactions, a pattern consistent with previously reported analogues. In contrast the parent NH heterocycle, oxazolin-2(3H)-one 4, exists as hydrogen bonded dimers of two closely similar independent molecules but an unusual type of disorder involving exchange of the ring O and NH positions results in a very high R factor.